2022
DOI: 10.3390/rs14010185
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Time-Lapse Changes with DAS Borehole Data at the Brady Geothermal Field Using Deconvolution Interferometry

Abstract: Distributed acoustic sensing (DAS) has great potential for monitoring natural-resource reservoirs and borehole conditions. However, the large volume of data and complicated wavefield add challenges to processing and interpretation. In this study, we demonstrate that seismic interferometry based on deconvolution is a convenient tool for analyzing this complicated wavefield. We also show the limitation of this technique, in that it still requires good coupling to extract the signal of interest. We extract cohere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…For instance, the 27.5-32 km segment has been replaced in 2017 and the natural burial of the cable into the soft sediment is not yet sufficient to provide good coupling. Other segments are probably hanging sections (around 20 km or 34 km) that do not record Scholte waves and display cable waves (Flores et al 2021;Chang & Nakata 2022). The strain-rate of these segments is set to 0.…”
Section: Da S Data a N D P Ro C E S S I N Gmentioning
confidence: 99%
“…For instance, the 27.5-32 km segment has been replaced in 2017 and the natural burial of the cable into the soft sediment is not yet sufficient to provide good coupling. Other segments are probably hanging sections (around 20 km or 34 km) that do not record Scholte waves and display cable waves (Flores et al 2021;Chang & Nakata 2022). The strain-rate of these segments is set to 0.…”
Section: Da S Data a N D P Ro C E S S I N Gmentioning
confidence: 99%
“…DAS has been successfully used for urban near‐surface characterization (Ajo‐Franklin et al., 2019; Dou et al., 2017; Fang et al., 2020), monitoring of unconventional reservoirs (Cheng et al., 2021; Daley et al., 2013; Jin & Roy, 2017), glacial deformation (Booth et al., 2020; Walter et al., 2020), and ocean dynamics (Cheng, Chi, et al., 2021; Lindsey et al., 2019; E. F. Williams et al., 2021; Viens et al., 2022). Recently, several DAS‐related feasibility studies have been conducted to characterize geothermal reservoirs (e.g., Chalari et al., 2019; Chang & Nakata, 2022; Feigl & Parker, 2019; Feigl & Team, 2017; Kasahara et al., 2020; Lellouch et al., 2021; Schölderle et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, ambient noises recorded by surface DAS systems have been studied and are widely used to derive shallow S-wave velocity structures and detect underground water 4 12 . However, few studies on borehole DAS ambient noise characteristics along depth have been reported 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%